Combined treatment with sacubitril/valsartan plus dapagliflozin in patients affected by heart failure with reduced ejection fraction - Jiang, Juan; Gao, Jie; Zhang, Xiuzhen; Li, Yuanmin; Dang, Heqin; Liu, Yanlin; Chen, Wenwen (Frontiers in Cardiovascular Medicine, 2023)
Background Data about real-world effects of combined therapy with sacubitril/valsartan plus dapagliflozin in patients affected by heart failure (HF) with reduced ejection fraction (HFrEF) has not been widely reported. In this article, the benefits of dapagliflozin and sacubitril/valsartan respect to improvements of cardiac function in patients with HFrEF would be investigated. Methods HF patients prescribed sacubitril/valsartan between January 2020 and January 2022 in a tertiary teaching hospital were selected using the Computerized Patient Record System. Patients were divided into two groups according to whether they were taking dapagliflozin. Clinical parameters at baseline and during follow-up were retrospectively collected and analyzed. Results Total of 136 consecutive patients were recruited for this study. 72 patients treated with sacubitril/valsartan and dapagliflozin were assigned to Group A, and another 64 patients receiving sacubitril/valsartan monotherapy were assigned to Group B. After treatment with sacubitril/valsartan plus dapagliflozin for a median follow-up period of 189 days (IQR, 180–276), significant improvements of cardiac function were achieved in Group A. Median N-terminal pro-B-type natriuretic peptide (NT-proBNP) level was significantly decreased from 2585 pg/ml (1014–3702.5) to 1260.5 pg/ml (439.8–2214.3) (P < 0.001). Mean left ventricular ejection fraction (LVEF) improved from 34.7 ± 4.6% to 39.2 ± 7.5% (P < 0.001). Mean daily dose of loop diuretics decreased from 37.1 ± 17.3 mg/day to 25.9 ± 18.5 mg/day (P < 0.001). Regarding safety, both systolic blood pressure (P = 0.002) and diastolic blood pressure (P = 0.002) significantly decreased. For patients in Group B, significant improvements in mean LVEF (P < 0.001), decreases in mean daily dose of loop diuretics (P = 0.001) and reductions in diastolic blood pressure (P = 0.023) were observed. Strikingly, both median Δ NT-proBNP (P = 0.04) and median Δ LAD (P = 0.006) in Group A were more pronounced in comparison with those seen in Group B. Conclusions The combined use of sacubitril/valsartan and dapagliflozin was associated with improved cardiac function in patents with HFrEF, and led to greater reductions in LAD and NT-proBNP levels compared to sacubitril/valsartan monotherapy. These findings suggest that the combination therapy may offer more potent cardiovascular benefits.